2018
DOI: 10.3389/fnana.2018.00001
|View full text |Cite
|
Sign up to set email alerts
|

Layer- and Cell Type-Specific Modulation of Excitatory Neuronal Activity in the Neocortex

Abstract: From an anatomical point of view the neocortex is subdivided into up to six layers depending on the cortical area. This subdivision has been described already by Meynert and Brodmann in the late 19/early 20. century and is mainly based on cytoarchitectonic features such as the size and location of the pyramidal cell bodies. Hence, cortical lamination is originally an anatomical concept based on the distribution of excitatory neuron. However, it has become apparent in recent years that apart from the layer-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 160 publications
3
94
0
Order By: Relevance
“…Outward currents could not be examined in Rheb CA neurons due to poor space clamp leading to unclamped firing upon depolarizing voltage pulses. Due to the large increase in Rheb CA neuron size, it was not surprising to find larger Kir-mediated currents, which are well-known to be expressed in control layer 2/3 pyramidal neurons as G protein inwardly rectifying K channels (46,47). However, finding HCN-mediated currents was surprising because control layer 2/3 pyramidal neurons are not known to express such currents, as confirmed here.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Outward currents could not be examined in Rheb CA neurons due to poor space clamp leading to unclamped firing upon depolarizing voltage pulses. Due to the large increase in Rheb CA neuron size, it was not surprising to find larger Kir-mediated currents, which are well-known to be expressed in control layer 2/3 pyramidal neurons as G protein inwardly rectifying K channels (46,47). However, finding HCN-mediated currents was surprising because control layer 2/3 pyramidal neurons are not known to express such currents, as confirmed here.…”
Section: Discussionsupporting
confidence: 73%
“…Identifying a cAMP-dependent excitability in Rheb CA neurons is tantalizing because cortical pyramidal neurons receive multiple inputs that activate receptors leading to cAMP increases. These inputs include noradrenergic and dopaminergic innervation from the locus coeruleus (e.g., (49,50)) and the ventral tegmental area (e.g., Gscoupled β1-and β2-adrenergic receptors and D1 and D5 receptors, see (47,51) for references).…”
Section: Discussionmentioning
confidence: 99%
“…Based on examination of its histological organization and cytoarchitecture, the neocortex can be divided into six layers. Histological layers contain multiple cell types, including excitatory neurons, inhibitory neurons, and glia, and layers can be differentiated based on cell type composition and density, as well as morphology and connectivity of resident cell types (DeFelipe and Fariñas, 1992;Harris and Shepherd, 2015;Narayanan et al, 2017;Radnikow and Feldmeyer, 2018) . Studies of postmortem brains from individuals with neuropsychiatric disorders have identified disease-associated changes in gene expression and synaptic structure that can be spatially localized to different cortical laminae (Sweet et al, 2010;Velmeshev et al, 2019) .…”
Section: Discussionmentioning
confidence: 99%
“…The spatial organization of the brain is fundamentally related to its function. This structure-function relationship is especially apparent in the context of the laminar organization of the human cerebral cortex where cells residing within different cortical layers show distinct gene expression patterns and exhibit differing patterns of morphology, physiology, and connectivity (DeFelipe and Fariñas, 1992;Harris and Shepherd, 2015;Narayanan et al, 2017;Radnikow and Feldmeyer, 2018) . To the extent that structure entrains function, understanding normal brain development as well as disorders of the central nervous system will require identifying the cell types that make up the brain, and ultimately linking functional correlates of individual cell classes with structural architecture.…”
Section: Introductionmentioning
confidence: 99%
“…106,107 An increased expression of mRNA for the CCL5 (RANTES) protein was recently noted in the neurons producing dopamine. 108 Chemokines show specificity for different types of leukocytes, which is particularly important in pathological conditions. Their contribution has been found in, eg, cardiovascular diseases, strokes and many inflammatory and autoimmune diseases, as well as in brain damage.…”
Section: Selected Chemokines In Strokesmentioning
confidence: 99%